(untitled) (Veterinary Science, 2025)
The aim of this study was to estimate the productive impact in the days before and after the onset of a mastitis event (ME), the electrical conductivity (EC) in the infected quarter during the event, and the economic cost it generates in a voluntary milking system (VMS) in Argentina. Data from 20 healthy cows and 20 cows that experienced ME (GM) on a VMS farm (Rafaela, Santa Fe) were used. Individual milk production (daily, per milking, and per quarter) and EC per quarter were evaluated at 10, -5, 0, 5, and 10 days from the onset of each ME. Milk production over a closed 305-day lactation period, the number of daily milkings, and the direct economic losses from ME were analyzed, considering the cost of treatments and milk loss. A total of 30 MEs were recorded. Production was lower in GM on days 0 and 5 (p< 0.05). Infected quarters showed lower production (p< 0.02) and higher EC (p< 0.01) in GM on all days. The production and EC of non-infected quarters, the number of daily milkings, and milk production over the closed lactation period were similar between groups (p> 0.05). Direct economic losses were approximately USD 116 per ME. Further adjustments in the mastitis detection index are required to better anticipate the diagnosis of MEs in VMS, thereby improving system efficiency and profitability.